PERLINDUNGAN HAKIM TERHADAP HAK-HAK ISTERI DALAM HAL SUAMI BERPOLIGAMI DI KOTA YOGYAKARTA - PRIHATI YUNIARLIN (Jurnal Media Hukum, 2012)
The research was aimed at identifying the protection for wives’ rights provided by judges in granting the permit for husbands’ polygamy and the effort done by wives in terms of unfulfilling their rights by husbands committing polygamy. This research was a normative law research which studied the law materials using the library research. The authoritative law sources were Koran and Hadits. The main resources were judges of religious courts. The results showed that: (1) the efforts attempted by the judges to protect the wives’ rights in terms of husbands wanting to do polygamy, that is: (a) the judges invited the wives or future wives to be asked about the statement on the willingness to become first and second wives and asked to give description about the risks of having husbands doing polygamy. Then, the statements were done in the written form; (b) the judges asked the wives’ brothers and sisters to be present in courts to provide a statement saying that the wives are suffered from mental disorders and unable to be present in the courts; (c) judges asked the husbands to provide written statements stating that they are willing to behave fairly and able to provide guarantee for the wives and children’s daily life needs. (2) wives’ efforts to defend their rights which are not fulfilled by their husbands doing polygamy were wives putting forward the sue for their rights to the religious courts for Muslims, and to the State Courts for non-Muslims.